2001
DOI: 10.1111/j.1939-1676.2001.tb01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Vascular Endothelial Growth Factor Concentrations in Healthy Dogs and Dogs with Hemangiosarcoma

Abstract: Vascular endothelial growth factor (VEGF) is a dimeric glycosylated polypeptide growth factor with potent angiogenic, mitogenic, and vascular permeability-enhancing properties specific for endothelial cells. In humans, VEGF seems to play a major role in tumor growth, and plasma concentrations correlate with tumor burden, response to therapy, and disease progression. This study compared plasma VEGF concentrations in healthy client-owned dogs (n = 17) to dogs with hemangiosarcoma (HSA; n 16). Dogs with HSA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 35 publications
10
59
0
3
Order By: Relevance
“…[26][27][28] Platelets and leukocytes have been demonstrated to store and release other angiogenic factors such as VEGF. 26,29 The use of platelet poor plasma has been advocated when assaying angiogenic factors to reduce errors associated with thrombocytopenia or sample handling. 28 A recent study did not find an association of leukocyte and platelet counts with plasma VEGF concentrations in dogs with HSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] Platelets and leukocytes have been demonstrated to store and release other angiogenic factors such as VEGF. 26,29 The use of platelet poor plasma has been advocated when assaying angiogenic factors to reduce errors associated with thrombocytopenia or sample handling. 28 A recent study did not find an association of leukocyte and platelet counts with plasma VEGF concentrations in dogs with HSA.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that endostatin is stored and released by activated platelets, systemic or localized consumptive coagulopathies, or immune-mediated platelet destruction, which are associated with HSA, and may be responsible for increases in endostatin seen in the diseased dogs in this study. 29 Attempts to correlate platelet counts with endostatin concentrations were not made because platelet counts were not performed in all healthy dogs, were not available from the medical records of all client-owned dogs, or were unable to be accurately reported because of sample handling or analytic errors. However, in dogs with complete laboratory evaluations, supportive evidence of disseminated intravascular coagulation was present in 4 of 12 (25%) dogs with HSA.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF levels were also studied in dogs suffering from haemangiosarcoma. Elevated levels were reported in dogs diagnosed with tumours, although no correlation was observed in terms of advancement of the disease or tumour size (4). Similar results were reported by Wergin and Kaser-Holtz (23), who demonstrated that the level of VEGF were undetectable in healthy dogs, while in dogs suffering from tumours, the obtained results were statistically significant (P = 0.008) and were within the range of 7.43 ± 11.2 pg/mL.…”
Section: Introductionmentioning
confidence: 91%
“…This ELISA has already been proven reliable for plasma VEGF evaluations in dogs in recent studies [6,7,27]. The VEGF ELISA was accomplished using the protocol from the manufacturer.…”
Section: Blood Samples and Vegf Assaymentioning
confidence: 99%